Preventing (panic) bank runs - Hubert J. Kiss; Ismael Rodríguez-Lara; Alfonso Rosa-Garcia (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
Andolfatto et al. (2017) proposes a mechanism to eliminate bank runs that occur as a coordination problem among depositors (Diamond and Dybvig, 1983). Building on their work, we conduct a laboratory experiment where we offer depositors the possibility to relocate their funds to a priority account. We find evidence that the mechanism reduces not only bank runs that occur because of a coordination problem among depositors but also panic bank runs (Kiss et al., 2018) that occur when depositors can observe the action of others.
Keywords: C91; D90; G21; G40; 330; bank run; coordination problem; panic behavior; experimental economics; policy tools; financial stability